Responsible AI in Security Pedagogy: A Proactive Ethical Framework for Mobile Learning and Simulation Platforms - Güttner, Luca; Röttinger, Raphael (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The proliferation of artificial intelligence (AI)-driven mobile learning systems for corporate security training presents new ethical challenges. This paper addresses the urgent need for a proactive ethical framework to govern these technologies. It systematically analyzes the key ethical dilemmas, including the tension between security monitoring and employee privacy, the risk of discriminatory outcomes from algorithmic bias, the ambiguity of accountability for AI-driven errors, and the lack of transparency inherent in ‘black box’ systems. This study proposes an actionable framework for the responsible design and deployment of these platforms. Drawing upon foundational principles from the UNESCO Recommendation on the Ethics of AI, the framework translates concepts like fairness, accountability, and human oversight into practical guidance, offering a tool for developers and practitioners to embed ethics into the entire technology lifecycle.